Mid-Infrared Coherent Sources and Applications - Ebrahim-Zadeh, Majid; Sorokina, Irina T. (NATO Science for Peace and Security Series B: Physics and Biophysics, 2008)
Coherent sources of mid-infrared (mid-IR) radiation are of great interest for a wide range of scienti?c and technological applications from spectroscopy and frequency metrology to information technology, industrial process control, pho- chemistry, photobiology and photomedicine. The mid-IR spectrum, which may be de?ned as wavelengths beyond ?2µm, covers important atmospheric windows, and numerous molecular gases, toxic agents, air, water, and soil pollutants, c- ponents of human breath, and several explosive agents have strong absorption ?ngerprints in this region. The development of practical coherent solid-state sources in the mid-IR can thus provide indispensable tools for a variety of - plications in environmental monitoring and pollution control, detection of water and soil contaminants, food quality control, agriculture and life sciences, and n- invasive disease diagnosis and therapy through breath analysis. Coherent mid-IR sources also offer important technologies for atmospheric chemistry, free-space communication, imaging, rapid detection of explosives, chemical and biological agents, nuclear material and narcotics, as well as applications in air- and sea-born safety and security, amongst many. The timely advancement of coherent mid-IR sources is, therefore, vital to future progress in many application areas across a broad range of scienti?c, technological, and industrial disciplines. On the other hand, more than 40 years after the invention of laser, much of the mid-IR spectrum still remains inaccessible to conventional lasers due to fun- mental limitations, most notably a lack of suitable crystalline laser gain materials.